The goals and the means: theoretical grounds for the category of social exclusion - Moreno Rubio, Mónica Eugenia (2023)
In this paper the results of a theoretical research on the category of social exclusion are presented, research performed from 2022 to early 2023. From a series of analysis related to the absence of a theoretical base for such category, the purpose was to identify, through document review, which theoretical background this category could be related with. The argument in this paper is that structural functionalism is an alternative for theoretical ground, because with Robert Merton was found that social exclusion is a problem addressed in his theory through the concept of anomie in his sociology of deviation.